Russia of PeterI: Gaining Great Power Status - P. A. Krotov (Vestnik MGIMO-Universiteta)
The article focuses on the issue of the international status of Russia during the reign of Peter the Great, which progressed from regional power in Eurasia to great power. It seeks to establish when and how Russia officially became a great power. The Poltava victory over the Swedish army (1709) showed that Russia had created the military-industrial poten- tial necessary for great power. The tsar gradually prepared the conditions for the proclama- tion of Russia as an empire and himself as an emperor. Arguably, the recognition of the title by the European states cannot be the main criterion for determining the time of Russia's transformation into a great power because recognizing the imperial title dragged on for sev- eral decades. The great power position of Russia and its new role in international relations began to find its reflection in the treaties between the leading European powers before the official recognition as an empire. International treaties of Russia with France, Austria, Prussia, Rzeczpospolita, Sweden, China, the Ottoman Empire and the Crimean Khanate show that for the first time, the new role of Russia as a great power, as the guarantor of the common Eu- ropean contractual system after the War of the Spanish Succession (1701 / 1702-1714) was enshrined in the Amsterdam Treaty (1717), which was concluded between Russia, France, and Prussia. The subsequent treaty, which had a similar significance for the assertion of the great power role of Russia in Europe, was signed in Vienna on July 26 (August 6), 1726, with another great power - Austria. The system of treaties that Russia was part of in the last years of the reign of Peter the Great was strikingly different from the one that was at the beginning of the reign. According to the Treaty of Nystad, Russia was registered as the guarantor of the new internal state structure of Sweden (which ceased to be an absolutist state) and even the guarantor of the rights to the throne of King Fredrik I (Article 7). Under the allied defense treaty with Sweden (February 22, 1724), both countries agreed to be the guarantors of the internal political structure of the Polish-Lithuanian Commonwealth. The analysis of docu- ments allows us to make a general conclusion that the treaties of Russia with other countries at the end of the reign of Peter the Great were one of the pillars of the system of international relations in Europe, which signified that Russia acquired new great power status.